On the non-Poissonian repetition pattern of FRB121102. Issue 4 (5th January 2018) - Oppermann, Niels; Yu, Hao-Ran; Pen, Ue-Li
Abstract: The Fast Radio Burst FRB121102 has been observed to repeat in an irregular fashion. Using published timing data of the observed bursts, we show that Poissonian statistics are not a good description of this random process. As an alternative, we suggest to describe the intervals between bursts with a Weibull distribution with a shape parameter smaller than one, which allows for the clustered nature of the bursts. We quantify the amount of clustering using the parameters of the Weibull distribution and discuss the consequences that it has for the detection probabilities of future observations and for the optimization of observing strategies. Allowing for this generalization, we find a mean repetition rate of $r=5.7^{+3.0}_{-2.0}$ per day and index $k=0.34^{+0.06}_{-0.05}$ for a correlation function ξ( t ) = ( t / t 0 ) k  − 1 .